Answer :

Let p(x) = x^{3} + 2x^{2} – 9x + 1

And g(x) = x + 4

Now put g(x) = 0

X + 4 = 0

X = –4

So remainder of p(x) when divided by g(x) = p(–4)

P(–4) = (–4)^{3} + 2(–4)^{2} – 9(–4) + 1

P(– 4) = –64 + 32 + 36 + 1

P(– 4) = 5

∴ – 5 should be added to p(x) so that p(x) is completely divisible by x + 4.

Rate this question :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x^{31</s}RS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x^{3}RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics